أثر الابتكار على التنافسية والتنمية الاقتصادية في الدول العربية خلال الفترة"2007-2018" - مخزومي، لطفي; عبداللاوي، عقبة (جامعة العربي بن مهيدي أم البواقي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
تهدف هذه الدراسة إلى قياس أثر الابتكار على التنافسية والتنمية الاقتصادية في الدول العربية للفترة 2007-2018. وقد تم قياس أثر الابتكار على المتغيرات المستقلة الآتية: مؤشر التنافسية العالمي، نمو نصيب الفرد من الناتج الحقيقي ومؤشر التنمية البشرية، كمؤشرات تقيس مستويات التنمية الاقتصادية. وقد تم استخدام القياس الاقتصادي لبيانات البانل اعتمادا على المفاضلة بين نموذج التأثيرات الثابتة والنموذج التجميعي ونموذج التأثيرات العشوائية. وقد خلصت الدراسة إلى وجود أثر إيجابي معنوي للابتكار على نصيب الفرد من الناتج، كما تشير النتائج إلى أثر سلبي للابتكار على التنافسية والتنمية البشرية في البلدان العربية.
This study aims to measure the impact of innovation on economic development and Competitiveness in Arab countries during the period (2007-2018). The impact of innovation has been measured on the following independent variables: Global Competitiveness Index, per capita GDP growth and human development index, as indicators that measure the economic development levels. The econometrics of the panel data was used based on the comparison between the fixed effects model, the pooled model, and the random effects model. The study concluded that there is a positive effect of innovation on the GDP per capita, and the results also indicate a negative impact of innovation on competitiveness and human development in the Arab countries.
Keywords: التنمية الإقتصادية -- التنافس الاقتصادي -- الدول العربية